Shared neural mechanisms between imagined and perceived egocentric motion – A combined GVS and fMRI study. (October 2019) - Macauda, Gianluca; Moisa, Marius; Mast, Fred W.; Ruff, Christian C.; Michels, Lars; Lenggenhager, Bigna
Abstract: Many cognitive and social processes involve mental simulations of a change in perspective. Behavioral studies suggest that such egocentric mental rotations rely on brain areas that are also involved in processing actual self-motion, thus depending on vestibular input. In a combined galvanic vestibular stimulation (GVS) and functional Magnetic Resonance Imaging (fMRI) study, we investigated the brain areas that underlie both simulated changes in self-location and the processing of vestibular stimulation within the same individuals. Participants performed an egocentric mental rotation task, an object-based mental rotation task, or a pure lateralization task during GVS or sham stimulation. At the neural level, we expected an overlap between brain areas activated during vestibular processing and egocentric mental rotation (against object-based mental rotation) within area OP2 and the Posterior Insular Cortex (PIC), two core brain regions involved in vestibular processing. The fMRI data showed a small overlap within area OP2 and a larger overlap within the PIC for both egocentric mental rotation against object-based mental rotation and vestibular processing. GVS did not influence the ability to perform egocentric mental rotation. Our results provide evidence for shared neural mechanisms underlying perceived and simulated self-motion. We conclude that mental rotation of one's body involves neural activity in the PIC and area OP2, but the behavioral results also suggest that those mental simulations of one's body might be robust to modulatory input from vestibular stimulation.